(untitled) (Journal of the College of Basic Education, 2020)
The aim of the present study is to determine the extent to which social intelligence contributes to the expressive performance of the sixth-grade students, and then to find out the difference in this intelligence among the students of the three branches (bio-literary). To achieve these two objectives The researcher chose the sample of (360) students from the sixth grade preparatory in the method of random progress and to detect the social intelligence The researcher prepared a measure of this intelligence, and to measure expression performance in the sixth-grade students preparatory researcher chose a subject of expression is ", the best people who sow the good, the good souls Sun wherever it went Lit ", and then The results of this research show that social intelligence has an influence on expressive performance and there was a difference between the three branches of social intelligence and the difference was for the benefit of The Biological Branch.